2020
DOI: 10.3390/ijms21218389
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characteristics of Exosomes Derived from Irradiated Mouse Organs and Their Role in the Mechanisms Driving Non-Targeted Effects

Abstract: Molecular communication between irradiated and unirradiated neighbouring cells initiates radiation-induced bystander effects (RIBE) and out-of-field (abscopal) effects which are both an example of the non-targeted effects (NTE) of ionising radiation (IR). Exosomes are small membrane vesicles of endosomal origin and newly identified mediators of NTE. Although exosome-mediated changes are well documented in radiation therapy and oncology, there is a lack of knowledge regarding the role of exosomes derived from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
0
31
1
Order By: Relevance
“…However, our understanding of EVs in the heart tissue remains limited, mainly due to technical challenges associated with isolation. EVs have been isolated from the heart using two main approaches, namely, mincing of fresh or frozen samples [34,[37][38][39], and enzymatic tissue digestion followed by mechanical dissociation and pipetting [40]. Such mechanical disruption invariably leads to cell rupture, thereby contaminating EV preparations with intracellular components and membranous debris, confounding their functional study and omics-based characterisation.…”
Section: Once Blood Has Clearedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our understanding of EVs in the heart tissue remains limited, mainly due to technical challenges associated with isolation. EVs have been isolated from the heart using two main approaches, namely, mincing of fresh or frozen samples [34,[37][38][39], and enzymatic tissue digestion followed by mechanical dissociation and pipetting [40]. Such mechanical disruption invariably leads to cell rupture, thereby contaminating EV preparations with intracellular components and membranous debris, confounding their functional study and omics-based characterisation.…”
Section: Once Blood Has Clearedmentioning
confidence: 99%
“…EVs have previously been isolated from hearts and cardiac tissues using mechanical dissociation [34,37,38,40] which invariably results in cell lysis and intracellular contamination of EV preparations. Indeed, other methods to isolate EVs from heart in this study involved tissue dicing, resulting in a high abundance of intracellular proteins associated with cardiac damage (troponins, lactate dehydrogenases, creatine kinases, myoglobin) [42][43][44] in isolated EVs (Figure S1).…”
Section: Once Blood Has Clearedmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the malignant tumors in the trials were always accompanied by metastasis to other sites, and on the basis of the expectation of powerful and sustained systemic therapeutic therapy, the AbE was further studied and enhanced for better clinical application. Studies showed that ionizing radiation in radiotherapy could induce the production of TEXs and change the exosomal secretion pattern and content of exosomes in local cells, leading to the AbE in abscopal tumor cells [ 57 ]. As the AbE was more often found in people with stronger immune systems [ 58 ], the AbE caused by radiation therapy could be explained by immune mechanisms.…”
Section: Tex-mediated Abscopal Effect and Immunomodulationmentioning
confidence: 99%
“…Exosome signalling is one of the mechanisms through which bystander effects can be transmitted. IR can cause increased exosome release that act as a messenger of bystander effects in both normal [44] and cancer cells [45]. Evidence for the importance of exosomes and exosomal content, particularly miRNAs, for transmitting bystander effects have been increased over the recent years.…”
Section: Introductionmentioning
confidence: 99%